Factor structure of swimmers for evaluating endurance and predicting 5000-m indoor and open water swimming performance - Vural, F.; Özkol, M. Z.; Aksit, T. (Baltic Journal of Health and Physical Activity, 2019)
Background: The purpose of the present study was to describe factor structures of swimmers for evaluating endurance. The second aim was to determine 5000m pool velocity (5000Vp) and 5000m open water swimming velocity (5000Vow).